2021
DOI: 10.1111/epi.16935
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood mononuclear cell activation sustains seizure activity

Abstract: Objective: The influx of immune cells and serum proteins from the periphery into the brain due to a dysfunctional blood-brain barrier (BBB) has been proposed to contribute to the pathogenesis of seizures in various forms of epilepsy and encephalitis.We evaluated the pathophysiological impact of activated peripheral blood mononuclear cells (PBMCs) and serum albumin on neuronal excitability in an in vitro brain preparation. Methods: A condition of mild endothelial activation induced by arterial perfusion of lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…SARS-COV-2 may severely hamper cerebral homeostasis upon entry into the CNS by destroying the blood-brain barrier (BBB) and glial limiting factor, activating the toll-like receptor (TLR), and ultimately leading to neuronal death ( 26 ). Several studies have reported that activation of TLR may promote epilepsy ( 27 , 28 ), while others have reported that immune cell and serum protein infiltration due to BBB destruction also exacerbates epilepsy ( 28 , 29 ). Moreover, SARS-COV-2 entry into the CNS could hamper the respiratory regulation center in the brain stem ( 30 ), which would significantly increase the risk of sudden epileptic death ( 31 ), and potentially contribute to increased mortality in SARS-COV-2 infected PWE.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-COV-2 may severely hamper cerebral homeostasis upon entry into the CNS by destroying the blood-brain barrier (BBB) and glial limiting factor, activating the toll-like receptor (TLR), and ultimately leading to neuronal death ( 26 ). Several studies have reported that activation of TLR may promote epilepsy ( 27 , 28 ), while others have reported that immune cell and serum protein infiltration due to BBB destruction also exacerbates epilepsy ( 28 , 29 ). Moreover, SARS-COV-2 entry into the CNS could hamper the respiratory regulation center in the brain stem ( 30 ), which would significantly increase the risk of sudden epileptic death ( 31 ), and potentially contribute to increased mortality in SARS-COV-2 infected PWE.…”
Section: Discussionmentioning
confidence: 99%
“…Since this is critical information necessary for comparing BBB function among the Ctrl and subjects with SZ, we have developed a semi-quantitative protocol using the Cavalieri estimator stereological function in Stereo Investigator software (MBF Bioscience, VT, United States). Similar to previous studies, our semi-quantitative protocol relies on the immunoreactivity demonstrated by the extravasated IgGs with neurons and neuropil ( Librizzi et al, 2021 ; Vila Verde et al, 2021 ). The Cavalieri estimator method is a proven unbiased stereological method used to calculate areas in tissue sections, and we have adopted it to estimate IgG leaked area fraction or the extent of BBB leak ( Cohen, 1992 ; No authors, 2021 ).…”
Section: Methodsmentioning
confidence: 93%
“…This indicated that inflammation reflected by NLR was involved in the pathophysiology of epilepsy. It is reported that serum albumin can extravasate from blood vessel into the brain parenchyma when the blood-brain barrier is dysfunctional, and this has been suggested to be involved in the pathogenesis of various types of epilepsy ( 33 35 ). In this study, we found that low serum albumin was associated with acute seizures, which effectively confirmed albumin extravasation after acute seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the activated microglia, reactive astrocytes and infiltrating immune cells release large amounts of pro-inflammatory mediators including IL-6, IL-1β, TNF-α, COX-2, HMGB1 and chemokines, inducing neuroinflammation through multiple signaling pathways. And the neuroinflammation can further increase excitability of the CNS, along with serum albumin extravasation ( 14 , 35 , 36 ). Thus, neuroinflammation can aggravate the severity, duration, and frequency of epileptic seizures and even lead to new-onset seizures ( 13 , 15 , 37 ).…”
Section: Discussionmentioning
confidence: 99%